Histopathologic aspects of experimental cysticercosis and in situ cytokines profile in C57BL/6 mice - Milhomem, Anália Cirqueira; Souza, Amanda Juliana Soaris de; Silva, Hidelberto Matos; Vinaud, Marina Clare; Oliveira, Milton Adriano Pelli de; Machado, Juliana Reis; Lino, Ruy de Souza, Júnior (Arquivos de Neuro-Psiquiatria, 2018)
Neurocysticercosis (NCC) is one of the parasitic infections that most affects the central nervous system. The knowledge regarding its immunopathogenesis and pathophysiology needs broadening. Taenia crassiceps cysticerci are used as the NCC experimental model. The aim of this work was to describe the general pathological processes and the in situ cytokine profile in C57BL/6 mice inoculated intracranially with viable T. crassiceps cysticerci. The histopathology analysis showed cysticerci in the extraparenchymal and intraventricular region, mononuclear inflammatory infiltration surrounding the parasite, microgliosis and meningitis. The analysis of the in situ immune profiles showed a predominance of the Th2 response. The IL-4 and IL-10 dosages were significantly increased in the infected group. The decrease in the INF-gamma dosage reflects the immunomodulation from the cysticerci. In conclusion, a T. crassiceps NCC infection in C57BL/6 mice triggers an inflammatory response, a predominance of Th2 type in situ profile, with mononuclear inflammatory cell infiltration, meningitis and microgliosis.
Keywords: neurocysticercosis; neglected diseases; Taenia